1998
DOI: 10.1002/clc.4960211111
|View full text |Cite
|
Sign up to set email alerts
|

Prior revascularization increases the effectiveness of enhanced external counterpulsation

Abstract: SummaryBtrckground and hypothesis: Enhanced external counterpulsation (EECP) is an effective noninvasive treatment for chronic angina. However, its usefulness has been felt to be limited in patients with angiographically demonstrated triplevessel coronary artery disease (CAD), in accord with the hypothesis that a patent vessel is necessary for transmission of the EECP-augmented coronary artery pressure and volume to the distal coronary vasculature.Md?ods: The effect of revascularization [coronary artery bypass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…A randomized clinical trial demonstrated significant improvement in the time to ST-segment depression during treadmill stress tests in the EECPtreated group compared with the control group (1). Several case study series and the International EECP Patient Registry, with more than 5,000 patients, have confirmed the benefits of EECP in providing symptomatic relief of angina (2, 7), improving blood flow to ischemic areas of myocardium [by radionuclide stress testing (6,12) and positron emission tomography (PET) scans (11)], eliminating or reducing nitrate use (10), as well as improving exercise tolerance (1,8). These effects have been reported to be sustained over several years (5,9).…”
mentioning
confidence: 99%
“…A randomized clinical trial demonstrated significant improvement in the time to ST-segment depression during treadmill stress tests in the EECPtreated group compared with the control group (1). Several case study series and the International EECP Patient Registry, with more than 5,000 patients, have confirmed the benefits of EECP in providing symptomatic relief of angina (2, 7), improving blood flow to ischemic areas of myocardium [by radionuclide stress testing (6,12) and positron emission tomography (PET) scans (11)], eliminating or reducing nitrate use (10), as well as improving exercise tolerance (1,8). These effects have been reported to be sustained over several years (5,9).…”
mentioning
confidence: 99%
“…Its use has been documented for more than four decades, but its use in the treatment of heart failure is incipient. Numerous small clinical studies of patients with stable chronic angina pectoris have shown improved cardiac perfusion imaging (2,(8)(9)(10)(11)(12)(13), reduction of angina class (2,9,10,12,13), increases in exercise tolerance (2,(8)(9)(10)(11), decreased use of nitroglycerine (10,12,13) and increased time to ST segment depression on stress testing with the use of EECP (2,8). Some of these studies have shown a sustained improvement for as long as five years after treatment (13).…”
Section: Eecp In Anginamentioning
confidence: 99%
“…8 The premise was that patients with more conduits tended to respond better than those who did not have these extra conduits. Patients with more extensive disease, such as those with triple-vessel disease, did not do quite as well as those with single-and doublevessel disease (Fig.…”
Section: Effectiveness Of Enhanced External Counterpulsationmentioning
confidence: 99%